PELUANG DAN TANTANGAN PERKEMBANGAN OBLIGASI SYARIAH (SUKUK) DI INDONESIA - Armadiyanti, Putri (Jurnal Akuntansi AKUNESA, 2013)
Currently the existence of Islamic bonds (sukuk) in Indonesia is popular eventhough the amount of its issuers are not as many as conventional bonds. Islamic bonds in Indonesia are valued prospective because the development of sukuk in Indonesia since 2002 until today has increased from year to year. Eventhough Islamic bonds have been prospective, investors who want to invest their money in sukuk have to be careful because in Indonesia the implementation of sharia agreement is still not fully implemented. In improving the development of Indonesia's sukuk, sukuk issuers and governments faced some of opportunities and challenges. This research aims to analyze what kinds of opportunities that can be maximilized and kinds of challenges that can be minimilized by governments and sukuk issuers in Indonesia. Key words: Sukuk, Opportunity, Challenge